Single Electron-Hole Pair Generation using Dark-Bright Solitons Conversion Control - S. Punthawanunt; R. Jomtarak; C. Teeka; P.P. Yupapin; J. Ali (My University, 2011)
In this paper, we present the new concept of single electron-hole pair generation by using dark-bright solitons conversion control based on microring resonator coupled to one arm MZI. By using some suitable parameters and found that the single electron-hole pair are seen, therefore, the single electron-hole pair generate can be storage and controll within the design system.
Keywords: Electron hole; Electron pair; Photonic and Optical Devices